Tacrolimus and the Risk of Solid Cancers After Liver Transplant: A Dose Effect Relationship. Issue 3 (3rd February 2015) - Carenco, C.; Assenat, E.; Faure, S.; Duny, Y.; Danan, G.; Bismuth, M.; Herrero, A.; Jung, B.; Ursic‐Bedoya, J.; Jaber, S.; Larrey, D.; Navarro, F.; et al.
<x xml:space="preserve">Abstract</x> Although increased rates of solid organ cancers have been reported following liver transplantation (LT), the impact of quantitative exposure to calcineurin inhibitors (CNI) remains unclear. We have therefore probed the relationship between the development of solid organ cancers following LT and the level of CNI exposure. This prospective single‐center study was conducted between 1995 and 2008 and is based on 247 tacrolimus‐treated liver transplant recipients who survived at least 1 year following surgery. The incidence of cancer was recorded, and the mean blood concentration of tacrolimus (TC) was determined at 1 and 3 years following LT. The study results indicate that 43 (17.4%) patients developed de novo solid cancers. Mean TC during the first year after LT was significantly higher in patients who developed solid organ tumors (10.3 ± 2.1 vs. 7.9 ± 1.9 ng/mL, p < 0.0001). Independent risks factors in multivariate analysis were tobacco consumption before LT (OR = 5.42; 95% CI [1.93–15.2], p = 0.0014) and mean annual TC during the first year after LT (p < 0.0001; OR = 2.01; 95% CI [1.57–2.59], p < 0.0001). Similar effects were observed in 216 patients who received tacrolimus continuously for ≥3 years. It appears therefore that CNI should be used with caution after LT, and that new immunosuppressive therapies could deliver significant clinical benefits in this regard.